Atypical case of hypermanganesemia with dystonia type 1: a treatable primary dystonia caused by inborn error of manganese metabolism - Kumar, Manish (International Journal of Contemporary Pediatrics, 2024)
Dystonia is one of the most common movement disorders in the pediatric age group. Dystonia with hypermanganesemia have polycythemia with deranged iron profile, chronic liver disease and basal ganglia hyperintensity on T1 weighted MRI brain image as characteristic finding. We are reporting one case of dystonia, lower limb weakness, polycythemia, and characteristic basal ganglia hyperintensity with a normal iron profile without liver involvement which diagnosed as inherited manganese (Mn) transporter defect due to homozygous mutations of SLC30A10 gene. Most of the reported cases of this mutation have reported decreased iron profile in their blood report and liver involvement contrary to our case. Intravenous disodium calcium edetate chelation and oral iron therapy led to a decrease in whole blood Mn level as well as clinical improvement in the patient. This is a rare disorder and is one of the potentially treatable inherited metal storage disorders and fatal if left untreated.